Pengaruh Variabel Internal UMKM terhadap Kualitas Laporan Keuangan - Nining Nur Safitri; Sri Dwi Estiningrum (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to determine the effect of the internal characteristics of SMEs on the quality of financial reporting. This research is a type of quantitative research. This research was conducted in sembung skin crackers, Tulungagung. The participants of this study were all SMEs in the leather cracker industry. To obtain 31 respondents, purposive sampling was conducted. Questionnaires were used to collect data, which were then routed to analysis. The results of this study indicate that the competence of human resources, accounting expertise, and use of technology all have a significant influence on the quality of information. The varying quality of financial reports has no effect on the quality of information. The implications of this research are expected to be a balancing material for SMEs to be able to improve financial reports.